EXPLORING THE FREQUENCY AND INDICATIONS OF PRIMARY CESAREAN SECTION IN UNSCARRED MULTIGRAVIDA PATIENTS: INSIGHTS FROM A TERTIARY CARE HOSPITAL (Journal of Medical & Health Sciences Review, 2025)
Objective: To determine the frequency and primary indications of caesarean section among unscarred multigravida patients and assess associated maternal and neonatal outcomes in a tertiary care hospital setting.Methodology: This cross-sectional study was conducted at the Department of Obstetrics and Gynaecology, Jinnah Postgraduate Medical Centre, Karachi, from January 2024 to July 2024. A total of 189 unscarred multigravida women with singleton pregnancies and cephalic presentation were included through non-probability consecutive sampling. Patients with previous uterine surgery or infertility history were excluded. Data on maternal demographics, indications for caesarean section, and neonatal outcomes including Apgar scores and birth weights were collected and analysed using SPSS version 25.Results: The mean maternal age was 28.94 ± 4.75 years. Most deliveries occurred at 36–40 weeks of gestation (69.31%). The most common indication for caesarean section was fetal distress (38.09%), followed by pathological cardiotocography (13.22%), non-progressive labor (8.46%), and antepartum eclampsia (6.34%). Apgar score >6 at birth was observed in 54.49% of neonates, which improved to 80.42% after 5 minutes. Maternal complications included fever (10.36%) and urinary tract infections (8.29%). A significant proportion of patients were unbooked (77.72%) and presented in emergency situations (95.85%).Conclusion: Fetal distress remains the leading cause of primary caesarean section among unscarred multigravidas. Early identification of risk factors, better antenatal care, and patient education can reduce unnecessary caesarean deliveries and improve maternal and neonatal outcomes.